The Impact of the Distribution Mechanism of University Seats Courses on Spatial Justice Achievement within the Region Case Study: Faculty of Engineering - Sulaimani University/ Silaimani Province – Kurdistan - Region of Iraq - Jalal, Shazad Jamal (Sulaimani Journal for Engineering Sciences, 2014)
The urban system in the Sulaimani Province is characterized the continuation of spatial dominance of Sulaimani city, since more than three decades and yet. And demonstrated that the application of the Zapf’s rule on the population of the ten largest urban centres, with comparing them by different time series. The phenomenon of dominance Has reflected picking all that is desirable in the province injustice spatially, through harvesting of students of the city for most of the seats at the Faculty of Engineering - University of Sulaimani (a desired college) by proportion more than twice the proportion of the population of the city at the expense of students who live outside the city within the province . The research the use of descriptive and analytical methodologies proved a variation in the percentage of getting those seats of the faculty by male students more than females by the largest proportion outside the city, as well as the high level of male education and increases the graduation rate as well. And appeared that male domination of accept in college took retreat in favour of females in the last decade of college life, especially in the last four years. And the continued application of the central mechanism of acceptance in higher education, are rendered to the result which that a continuation of the regional variation between the Sulaimani city and areas beyond it within the Province. As this mechanism help in the formulation of structuring technical staff (Engineering) of the city more regularly with compared to areas beyond it, and increase the speed direction of the development process in the rhythm is very different with the line of general development in the province. That caused the disturbance of balance in spatial justice towards the city’s benefit within the Province, due to the presence of continuation slowing down of spatial development in outside areas of the city.